Effects of concurrent exercise on cardiometabolic status during perimenopause: the FLAMENCO Project. (2nd November 2018) - Coll-Risco, I.; Borges-Cosic, M.; Acosta-Manzano, P.; Camiletti-Moirón, D.; Aranda, P.; Aparicio, V. A.
Abstract: Objectives: The aim of this study was to evaluate the influence of a 4-month concurrent exercise training program on cardiometabolic status in perimenopausal women. Methods: The participants ( n  = 150) were randomized into counseling ( n  = 75) and exercise ( n  = 75) groups. The exercise group followed 4-month (3 days/week, 60 min/session) concurrent training. The counseling group attended conferences on a healthy lifestyle. We determined plasma glucose, total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides, and C-reactive protein, and measured blood pressure and the resting heart rate. Results: In the per-protocol analyses, the exercise group showed lower LDL-C concentrations than the counseling group when the model was further adjusted for the baseline values and diet (10.2 mg/dl; 95% confidence interval −19.4, −0.96; p  = 0.031). Borderline significant total cholesterol and diastolic blood pressure were reduced in both groups with better results in exercise group ( p  = 0.068 and p  = 0.090, respectively). Conclusion: The present findings suggest that the concurrent exercise training program could improve plasma glucose, lipid profile, CRP, and systolic and diastolic blood pressures in the exercise group. These results also suggest the importance of a healthy diet and active behavior during menopause, as improvements in both the exercise and the counseling group were observed. Future analysis should combine both interventions in search of better results.